STRATIFICATION OF YOUTH PERIODS AND AGE CRISES - Murkhashev Akhmadkhan Olimjon ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
To find an answer to this question depends on understanding the nature of human psychic development. One of these points of view mentions the invariability of the age period. This perception of age is closely related to the understanding of mental development as a natural biological process. One of the opposite points of view rejects the concept of age altogether.